Akuntansi Syariah sebagai Instrumen Transparansi Keuangan di Masjid Cheng Ho Palembang: Islamic Accounting as an Instrument of Financial Transparency in Cheng Ho Mosque Palembang - Arwandi, Safta; Azzahra, Rissa; Ilmiyah, Nazihah Nur; Azwari, Peny Cahaya (Institut Agama Islam Negeri Kerinci, 2025)
Purpose: Mosque financial management is often still carried out in a simple manner, so that transparency and accountability are not yet fully realized. This condition can lead to limited information for congregations and the community. This study focuses on understanding the role of sharia accounting in improving financial transparency at the Cheng Ho Mosque in Palembang. Design/Methodology/Approach: This study uses a qualitative research method with a descriptive approach. The data used in this study are primary and secondary data, collected through observation, interviews, and documentation. There is one informant in this study, namely the mosque administrator who has direct authority over the financial management of the Cheng Ho Mosque in Palembang. Findings: This study found that the Cheng Ho Palembang Mosque has implemented sharia financial transparency that can be accessed by worshipers in their financial management in the Maslam application. Research Implications: Cheng Ho Mosque Palembang needs to utilize financial reports as a routine evaluation tool to improve the effectiveness and efficiency of fund management. Thus, the mosque can ensure that financial activities run in accordance with sharia accounting principles and support better decision making.